Feasibility and acceptability of peer-delivered interventions using mHealth for PrEP services among adolescent girls and young women in DREAMS program in Botswana - Marie-Claude C. Lavoie; Lillian Okui; Natalia Blanco; Kirsten Stoebenau; Jessica F. Magidson; Gadzikanani Gokatweng; Kaizer Ikgopoleng; Manhattan E. Charurat; Ndwapi Ndwapi (Taylor & Francis Group, 2023)
Background Adolescent girls and young women accounted for 25% of all new HIV infections despite representing only 10% of the population in Sub Saharan Africa. PEPFAR has launched the Determined, Resilient, Empowered, AIDS-free, Mentored, and Safe (DREAMS) initiative, a comprehensive HIV prevention program including PrEP services. Among adolescent girls and young women, PrEP adherence is currently sub-optimal. Tailored strategies for adolescent girls and young women to improve access and use of PrEP delivery are urgently needed to maximise its potential. Recommended interventions include peer-delivered interventions using mobile technology. However, data on the feasibility and acceptability of this approach is limited for SSA. Objectives We assessed the feasibility and perceived acceptability of providing mHealth peer-delivered interventions to support PrEP services among adolescent girls and young women in Botswana. Methods This cross-sectional study included HIV-negative women aged 18-24 years old seeking health services at DREAMS-supported facilities. Participants completed a survey assessing the feasibility and perceived acceptability of the mHealth peer-delivered interventions, which included the Acceptability of Intervention Measure (AIM). Descriptive analyses were performed. Results A total of 131 participated in the study. Overall, 89% owned a mobile phone (feasibility). There was no difference in cell phone ownership between participants from rural and urban settings. Among participants, 85% reported interest in participating in a mHealth peer-delivered intervention if it was available to them. Regarding perceived acceptability for mHealthpeer support groups for PrEP, the average score on the AIM was 3.8 out of 5 (SD = 0.8). Conclusion mHealthpeer-delivered interventions appear to be feasible and perceived acceptable among adolescent girls and young women in Botswana. This modality should be incorporated into PEPFAR's programmatic toolkit of implementation strategies to improve PrEP services.